2018
DOI: 10.18203/2349-2902.isj20180371
|View full text |Cite
|
Sign up to set email alerts
|

Pleomorphic adenoma of submandibular gland: not so common occurrence

Abstract: INTRODUCTIONSalivary gland tumors are uncommon and comprise only 1-4% of head-face-neck tumors. Majority of the salivary gland tumors affect parotid gland with more than 70% of the cases. Several studies have been conducted on the tumors of the parotid and minor salivary glands, but very few reports in the literature have focused on submandibular gland tumors as they are rare and are usually grouped with other salivary glands. Submandibular gland is affected in 5-10% of the cases with pleomorphic adenoma being… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…Temporary paralysis may resolve spontaneously within a period of 3 months. 7 Parag et al study showed, complications like neuropraxia/paresis developed in marginal mandibular branch of facial nerve in 5 (10%) patients within first 24 hours postoperatively and while it completely resolved within 3-6 month. Other complications which developed were hematoma (2%) and surgical site infection (6%).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Temporary paralysis may resolve spontaneously within a period of 3 months. 7 Parag et al study showed, complications like neuropraxia/paresis developed in marginal mandibular branch of facial nerve in 5 (10%) patients within first 24 hours postoperatively and while it completely resolved within 3-6 month. Other complications which developed were hematoma (2%) and surgical site infection (6%).…”
Section: Discussionmentioning
confidence: 97%
“…Other complications which developed were hematoma (2%) and surgical site infection (6%). 7 Osunde et al study showed malignant changes can occur in PA and include three distinct pathologic entities: Carcinoma arising in PA, which has been reported to occur in about 3-4%, carcinosarcoma, and benign metastasizing PA. Malignant changes were found in only 10% of the giant PA cases reviewed by Schultz-Coulon. The incidence of malignancy frequently shows a correlation between the length of the history of PA and the development of a carcinoma.…”
Section: Discussionmentioning
confidence: 99%